Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
mình sửa đề số cuối nhé
\(\dfrac{2}{3}\left(\dfrac{1}{5}-\dfrac{1}{8}+\dfrac{1}{8}-\dfrac{1}{11}+...+\dfrac{1}{90}-\dfrac{1}{93}\right)\)
\(=\dfrac{2}{3}\left(\dfrac{1}{5}-\dfrac{1}{93}\right)=\dfrac{176}{1395}\)
\(xy-x+y=4\\ \Rightarrow x\left(y-1\right)+\left(y-1\right)=3\\ \Rightarrow\left(x+1\right)\left(y-1\right)=3\)
Vì \(x,y\in Z\Rightarrow\left\{{}\begin{matrix}x+1,y-1\in Z\\x+1,y-1\inƯ\left(3\right)\end{matrix}\right.\)
Ta có bảng:
x+1 | -3 | -1 | 1 | 3 |
y-1 | -1 | -3 | 3 | 1 |
x | -4 | -2 | 0 | 2 |
y | 0 | -2 | 4 | 2 |
Vậy \(\left(x,y\right)\in\left\{\left(-4;0\right);\left(-2;-2\right);\left(0;4\right);\left(2;2\right)\right\}\)
\(2^x-2^{x-2}=96\\ \Rightarrow2^x-2^x:4=96\\ \Leftrightarrow2^x-2^x.0,25=96\\ \Rightarrow2^x\left(1-0,25\right)=96\\ \Rightarrow2^x.0,75=96\\ \Rightarrow2^x=128\\ \Rightarrow2^x=2^7\\ \Rightarrow x=7\)
\(\left(3x+6\right)-35=-2\\ \Rightarrow3x+6=-2+35\\ \Rightarrow3x+6=33\\ \Rightarrow3x=33-6\\ \Rightarrow3x=27\\ \Rightarrow x=27:3\\ \Rightarrow x=9\)
TL :
( 3x + 6 ) - 35 = -2
3x + 6 = -2 + 35
3x + 6 = 33
3x = 33 - 6
3x = 27
x = 27 : 3
x = 9
Vậy x = 9
HT